Masdddho's Personal Branding Strategy as a Newcomer Pop Javanese Musician through TikTok - Aisah Detri; Denis Firmansyah; Khaerudin Imawan (Publikasi Indonesia, 2025)
This research aims to authentically understand the personal branding strategy employed by Masdddho, a rising musician in the Javanese pop genre, through the TikTok platform. Applying the theory of Authentic Personal Branding proposed by Rampersad and using a qualitative research method, this study was conducted through interviews, social media analysis, and documentation with Masdddho as the main informant. The results show that Masdddho embodies characteristics aligned with the concept of authentic personal branding, namely authenticity, integrity, consistency, specialization, authority, distinctiveness, visibility, perseverance, relevance, kindness, and performance. As a newcomer, Masdddho has successfully built a strong personal brand through the excellence of his vocal character, principles, appearance, creativity, and musical quality. His success is reflected in his TikTok following, with 1.6 million followers on his personal account and 492.6 thousand followers on his production team's account. In addition, Masdddho has received prestigious awards, including the AMI Awards for Best Solo/Group/Collaboration Koplo Artist and Favorite Music Video. These findings indicate that implementing an authentic personal branding strategy significantly contributes to a musician’s visibility and success in the era of social media.